(3bGfhf GdJLGQI GdEdcJQhfjI hGdJhbjY GdEdcJQhfj hbGfhf GdedcjI GdacQjI hGdCOHjI (B/s - (3CMeO, GHQGgje SjOs ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2005)
(3GJaGbjI (BTRIPS- (3eYGgOGJ GdhjHh HTCf Mb GdeDda(B- (3eYGgOI GdhjHh HTCf GdCOGA hGdJSLjd GdUhJj(B- (3bGfhf GdChfSjJQGd GdfehPLj HTCf GdJhbjYGJ GdEdcJQhfjI(B- (3GdJYdjb Ydi bGfhf GdJhbjYGJ GdEdcJQhfjI aj GdJLGQI GdYGdejI hGdeMdjI(B- (3CMcGe eTQhY GJaGbjI GdLhGfH GdbGfhfjI ddJLGQI GdEdcJQhfjI(B- (3dLfI GdGee GdeJMOI dbGfhf GdJLGQj(B- (3GdbGfhf Qbe(B10 (3dSfI (B2004 (3HJfXje GdJhbjY GdEdcJQhfj aj LeghQjI eUQ GdYQHjI(B.s
Keywords: (3GdJLGQI GdEdcJQhfjIs; (3GdJhbjY GdEdcJQhfjs; (3GdbGfhf GdJLGQjs; (3GdedcjI GdacQjI(B- (3bhGfjf hJTQjYGJs